Menyimak (Kembali) Integrasi Budaya di Tanah Batak Toba - Sugiyarto Sugiyarto (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2017)
Toba Batak Land is one of the areas in North Sumatra Province that have dominant culture characterized by among others by: (1) the majority of indigenous Batak people; (2) Batak culture (Toba) becomes a reference for the behavior of the population in interacting in local public places; (3) Batak leadership is implemented based on elements of Batak culture. In the meantime, there are also ethnic groups of immigrants, Hindus and Christians. The embodiment of ethnicity of ethnic groups of migrants finally can integrate culturally because there are similarities of divine concepts such as Trimurti on Hindu teachings, Debata na tolu on the teachings of Parmalin in Batak Toba, as well as the Trinity in the teachings of Christians